Avaliação da atividade antibacteriana, citotóxica e antitumoral da Kombucha de chá preto - (:unkn) unknown (Universidade Estadual de Goiás, 2022)
Kombucha is a fermented probiotic refreshing drink, with a bittersweet flavor, its fermentation takes place from a symbiotic culture of bacteria and yeast. A study was carried out to evaluate the antimicrobial and antitumor activity of the kombucha drink, also analyzing the toxicity test against the microcrustacean Artemia salina, pH analysis and alcohol content. The determination of the antimicrobial activity of kombucha was carried out by the microdilution test in broth, according to the protocol recommended by the Clinical and Laboratory Standard Institute (CLSI), where a favorable antimicrobial action was observed for the bacteria Staphylococcus aureus and Klebsiella pneumoniae, at a concentration of 60 μg.mL-1 it was verified that at this concentration kombucha has a bacteriostatic action, but not a bactericidal one. In the antitumor bioassay, kombucha showed a maximum inhibition of 79.36% at a concentration of 1,500μL. The pH of kombucha showed values of 6.7 and 3.2 for days 1 and 21 of fermentation, respectively, values considered ideal to ensure a pleasant taste. The alcohol content value found was 0.0% v/v, which is in line with what is recommended by brazilian legislation, considering the health and safety precautions associated with the ingestion of alcoholic beverages. It is concluded that the kombucha drink has antimicrobial and antitumor actions, but that need to be better elucidated in favor of our health.
Evaluation of antibacterial, cytotoxic and antitumor activity of black tea Kombucha
Keywords: Kombucha; Bebida fermentada; Probióticos; Saúde; Fermented beverage; Probiotics; Health; CIENCIAS DA SAUDE